High Migratory Potential Of Fall Armyworm In West Africa Despite Stable Temperatures And Widely Available Year-Round Habitats. - Fan-Qi, G.; Chen, H.; Kyerematen, R.; Hu, G.; Early, R.; Chapman, J.W. (Insect Science, 2024)
The fall armyworm (FAW), an important migratory pest native to the Americas, was first detected in a nonnative region (West Africa) in 2016. In the following years, it quickly spread to multiple regions worldwide. FAW exhibits long-distance sea sonal migration in both the Americas and Asia, primarily to take advantage of suitable seasonal habitats as they appear along the migratory pathways. Tropical West Africa ex periences minimal annual temperature variation and has widely distributed potential year-round habitats, leading us to hypothesize that the migration capacity of FAW populations in this region may be substantially reduced. To test our hypothesis, we assessed the flight performance of FAW collected from Ghana in West Africa with tethered flight mills and compared it to that of a FAW population from southern China. Additionally, we quanti fied the relationships between morphological characteristics and flight performance of the FAW from Ghana. Based on observed flight behaviors, we categorized FAW into migratory and non-migratory types. The flight capabilities of first-generation Ghanaian FAW bred in the laboratory were similar to that of the field population from Yunnan, South West China, with migrants making up the majority. However, after several generations of laboratory rearing, the flight capability of the Ghanaian population significantly declined, primarily due to a marked increase in the proportion of non-migratory individuals. The low correlation between morphological variables and flight duration suggests that genetic factors likely determine most variations in flight propensity. The results of this study in dicate that FAW with high migratory capacity in West Africa is likely to pose a threat to crops in eradication zones and neighboring uninvaded areas and may possibly be capable of crossing the Sahara Desert and invading Europe. Therefore, it is crucial to establish comprehensive pest early warning and management systems.
Research Article
Keywords: China; Fall Armyworm; Flight Performance; Ghana; Migration; Morphological Features